The social function of the act of educating: the teaching practice and its link with the exercise of criticality (Research, Society and Development, 2022)
This work seeks to reflect on the teaching practice in education and the act of educating. To this end, the work weaves discussions around three main points: the social function of teaching practice, the act of educating and teacher training. Firstly, it became evident that an education is not conceived where the teacher is not aware of the conceptions that permeate his work. In this process, the school plays two fundamental roles in society: socializing and democratizing access to knowledge and promoting moral and ethical construction in students. Then, the need to understand and carry out a democratic educational practice was emphasized, guided by humanizing principles, by virtues, focusing on meaningful knowledge for the student. And, finally, the need to perceive the educational reality on the school floor was portrayed, emphasizing the importance of reflection and action from the continuing education of teachers, whose objective involves the growth of our lives in all spheres. It is important to emphasize that the certifications acquired during the training process greatly contribute to the success of a career, but they are not the only ones responsible for this to happen. Seeking different ways to acquire personal skills that reflect on teaching is fundamental. Educating in a liberating way is to contribute to the formation of citizens capable of building an autonomous and fair society, it is to seek paths that present meanings for students, which are the key to education.